A note on connectivity and stability in dynamic network formation - Tackseung Jun; Jeong-yoo Kim (Games, 2020)
We consider the dynamic network formation problem under the requirement that the whole network be connected and remain connected after q nodes are destroyed. We propose the concept of dynamic Cq-stability and characterize dynamic Cq-stable networks for any qÏ0. Comparison with the outcome in the static model is also discussed.
Keywords: C72; 330; connectivity; network formation; dynamic Cq-stability